A new software tool for the analysis of noble gas data sets from (ground)water - Jung, Michael; Aeschbach, Werner (Environmental modelling & software, 2018)
In this article we present the software PANGA which is a new open-source tool for the evaluation of noble gas data from (ground)water samples. In addition to most of the features of traditionally used software like NOBLE, it includes among others easy-to-use methods for Monte Carlo simulations and analyses, as well as support for newer excess air models and ensemble fits. We verify PANGA's results for two data sets by comparing them with the results of NOBLE, using different excess air models. We conclude this study with a set of recommendations for the evaluation of noble gas data sets, giving detailed step-by-step instructions, including descriptions of the Monte Carlo patterns most commonly observed.
Gesehen am 12.03.2019